Multidimensional and multicultural media literacy. Social challenges and communicational risks on the edge between cultural heritage and technological development - Reia-Baptista, Vítor (2017)
For quite some time, we have been “observing some of the new environments of media exposure”1 and we may probably say, by now, that the multidimen- sional forms of media exposure that can be experienced daily through the use of different technologies and technological devic es are not always signs of cor- responding multicultural media literacy phenomena. We also know, from earlier contexts and attempts to combine media, technology and literacy inside different cultural environments of different societies and public communication spheres, that the ‘empowerment’ effect that could be expected to arise from those expo- sure situations is not always a factor of cultural enrichment and, on the contrary, it assumes too many times the character of some alienation phenomenon or, at least, an alienator mode of media appropriation.